The Src Homology 2 Domain of Vav Is Required for Its Compartmentation to the Plasma Membrane and Activation of C-Jun Nh2-Terminal Kinase 1 - Arudchandran, Ramachandran (The Rockefeller University Press, 2000)
Vav is a hematopoietic cell–specific guanine nucleotide exchange factor (GEF) whose activation is mediated by receptor engagement. The relationship of Vav localization to its function is presently unclear. We found that Vav redistributes to the plasma membrane in response to Fc∈ receptor I (Fc∈RI) engagement. The redistribution of Vav was mediated by its Src homology 2 (SH2) domain and required Syk activity. The Fc∈RI and Vav were found to colocalize and were recruited to glycosphingolipid-enriched microdomains (GEMs). The scaffold protein, linker for activation of T cells (LAT), and Rac1 (a target of Vav activity) were constitutively present in GEMs. Expression of an SH2 domain–containing COOH-terminal fragment of Vav inhibited Vav phosphorylation and movement to the GEMs but had no effect on the tyrosine phosphorylation of the adaptor protein, SLP-76 (SH2 domain–containing leukocyte protein of 76 kD), and LAT. However, assembly of the multiprotein complex containing these proteins was inhibited. In addition, Fc∈RI-dependent activation of c-Jun NH2-terminal kinase 1 (JNK1) was also inhibited. Thus, Vav localization to the plasma membrane is mediated by its SH2 domain and may serve to regulate downstream effectors like JNK1.